Persistent Content-based Information Dissemination in Hybrid Vehicular Networks - Leontiadis, Ilias; Costa, Paolo; Mascolo, Cecilia (The 7th IEEE International Conference on Pervasive Computing and Communications (PERCOM'09), Galveston, Texas, USA, March 2009., 2009)
Content-based information dissemination has a potential number of applications in vehicular networking, including advertising, traffic and parking notifications and emergency announcements. In this paper we describe a protocol for content based information dissemination in hybrid (i.e., partially structureless) vehicular networks. The protocol allows content to ``stick'' to areas where vehicles need to receive it. The vehicle's subscriptions indicate the driver's interests about types of content and are used to filter and route information to affected vehicles. The publications, generated by other vehicles or by central servers, are first routed into the area, then continuously propagated for a specified time interval. The protocol takes advantage of both the infrastructure (i.e., wireless base stations), if this exists, and the decentralized vehicle-to-vehicle communication technologies. We evaluate our approach by simulation over a number of realistic vehicular traces based scenarios. Results show that our protocol achieves high message delivery while introducing low overhead, even in scenarios where no infrastructure is available.